PROFIL KEMAMPUAN BERPIKIR KRITIS MAHASISWA UNIVERSITAS HASYIM ASY’ARI JOMBANG PADA MATAKULIAH BIOLOGI DASAR - Hayati, Nur; Berlianti, Nindha Ayu; Wijayadi, Andri Wahyu (Universitas Negeri Malang, 2019)
One of the most important skills which is needed to face this 21st centurychallenge is critical thinking since it is very important to solve problems. This research is conducted to find out the critical thinking skill of the Science Department students at Universitas Hasyim Asy’ari (UNHASY) Jombang who took Basic Biology. This research is a survey research and conducted during even semester 2018/2019. The number of the research subject is 57 students. The researchers use essay/subjective test as research instrument to measure the students’ critical thinking. Then, the data was analyzed descritively. Based on the research, the researchers found that the students’ critical thinking is at indicator range 2,92 which means undeveloped. The total percentage of students’ critical thinking skill which is at undeveloped level is 49,12% while the other one which is at well developed level is 50,88%.